Repeated Type III Burst Groups Associated with a B-Class Flare and a Narrow-Width CME - Pohjolainen Silja; Mckay Derek; Sheshvan Nasrin Talebpour; Monstein Christian (Springer Dordrecht, 2025)
We have analysed a solar event from 27 September 2021, which included a small GOES B-class flare, a compact and narrow-width CME, and radio type III bursts that appeared in groups. The long-duration, repeated metric type III burst emission indicates continuous electron acceleration at high altitudes. The flaring active region was surrounded by strong magnetic fields and large-scale loops, which guided the outflow of the CME plasmoid and hence the narrow, bullet-like appearance of the CME. Radio imaging and EUV observations confirmed the direction of particle propagation and the depletion of matter from the solar source region. We observed V-shaped type III burst emission lanes, which also explain the field configuration and suggest a possible location for repeated reconnection that occurred at a constant altitude.